Convergence of locally and globally interacting Markov chains - Hans Föllmer; Ulrich Horst (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
We study the long run behaviour of interactive Markov chains on infinite product spaces. In view of microstructure models of financial markets, the interaction has both a local and a global component. The convergence of such Markov chains is analyzed on the microscopic level and on the macroscopic level of empirical fields. We give sufficient conditions for convergence on the macroscopic level. Using a perturbation of the Dobrushin-Vasserstein contraction technique we show that macroscopic convergence implies weak convergence of the underlying Markov chain. This extends the basic convergence theorem of Vasserstein (1969) for locally interacting Markov chains to the case where an additional global component appears in the interaction.
urn:nbn:de:kobv:11-10049437
Keywords: 330; Markov chains on infinite product spaces; convergence of Markov chains; contraction techniques; Gibbs measures